The Display System of a Patient's History Using the RFID and Linux - Soo Young Ye; Heung-kuk Jo (International Journal of Distributed Sensor Networks)
It is important for doctors to see a patient's medical history when the patient visits the hospital. Currently, doctors research and compare information on their patient's condition through the patient or medical history chart. This method can cause confusion when the patient has several namesakes which can lead to medical errors and malpractice. To prevent such accidents, doctors should have access to the accurate history of their patients through an independent recognition system at any time or any place. Examples of such independent recognition systems are the RFID system, a compacted embedded system, and RFID reader and a TFT-LCD monitor with a unified single system. In this study, to record a patient's medical history, an RFID monitoring system with a carrier frequency of 125 kHz a PXA255 ARM chip, and a 64 Mbyte SDRAM was configured and operated as an embedded Linux system. These two systems were interlocked to read the patient's arm tags. The interlocked system can obtain patients' medical history from a database and display it on a monitor. The advantage of this system is that it does not need a computer and can be implemented with only a hand-held device. Its performance analysis chart shows the result from the experimental device and the results shown with photographs.